KONSEP JODOH, SAKINAH, MAWADAH, dan RAHMAT (Analisis Teks Ayat al-Qur’an dengan Pendekatan Tafsir Madlu’i) - Rahman, Fawait Syaiful (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2021)
Abstract Islam limits the patterns of interaction between men and women outside of marriage so that each other's honor can be maintained. In humans, there is a tendency of animal tendencies that have the potential to lead to prohibited cases (mungkarat or muharramat). Islam also regulates the provisions if a man and woman want a halal relationship as well as a reward value in the framework of marriage. An ideal marriage is generally defined as a marriage that is the result of one's own choice without any outside intervention, the two partners are never heard of fighting and arguing, and a married couple is supported by an established economy, such family conditions are considered ideal families. After several weeks or more, the news was heard that the husband and wife were divorced, even though at the beginning of the marriage they had received a prayer "hopefully they will become a sakinah family, mawadah, wa-rahmah and mate in the hereafter" could not prevent the intention to separate. The research method in this article uses a qualitative literature approach. The conclusion from the study and analysis of the text of the verses of the Koran is as follows that the mention of the concept of mate and the concepts of sakinah, mawadah, warahmah in the Koran are different. The concept of mate is said to use Arabic khalaqah, and the concepts of sakinah, mawadah, warahmah are spoken in Arabic ja'ala. The concept of a mate that is expressed using khlaqah means that it is the personal right of Allah SWT and humans do not have the effort to intervene, while the concepts of sakinah, mawadah, warahmah in marriage need human intervention so that forming and creating an ideal family requires effort and intervention from both. couple.